The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.soard.2019.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sleeve gastrectomy induces sustained changes in gray and white matter brain volumes and resting functional connectivity in obese patients

Abstract: Background: Obesity is associated with decreased brain gray-(GM) and white-matter (WM) volumes in regions. Laparoscopic sleeve gastrectomy (LSG) is an effective bariatric surgery associated with neuroplastic changes in patients with obesity at 1 month postLSG. Objective: To investigate whether LSG can induce sustained neuroplastic recovery of brain structural abnormalities, and whether structural changes are accompanied by functional alterations. Setting: University hospital, longitudinal study. Methods: Struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…A designated clinician rated the severity of the participants' anxiety using the Hamilton Anxiety Rating Scale (HAMA) and depression using the Hamilton Depression Rating Scale (HAMD) 26 . The anxiety and depression measures were used to exclude subjects with a psychiatric disorder.…”
Section: Methodsmentioning
confidence: 99%
“…A designated clinician rated the severity of the participants' anxiety using the Hamilton Anxiety Rating Scale (HAMA) and depression using the Hamilton Depression Rating Scale (HAMD) 26 . The anxiety and depression measures were used to exclude subjects with a psychiatric disorder.…”
Section: Methodsmentioning
confidence: 99%
“…The first case of intussusception complicating pregnancy following LRYGB was reported in 2007 by Wax et al. [ 6 ]. As far as we have known, only 23 cases have been described in the literature [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy predisposes to obstruction after RYGB remains a matter of debate, particularly regarding intussusception. A review of the literature regarding intussusception after RYGB in pregnant women reported that most is retrograde and in the jejunojejunostomy [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic sleeve gastrectomy (LSG) is one of the most performed procedures in clinical practice, and normally lead to weight loss between 20 and 35% of original weight (Peterli et al, 2018). Growing neuroimaging evidence indicates that LSG induces brain functional and structural alterations in regions and circuits implicated in reward (caudate, ventral tegmental area) (Faulconbridge et al, 2016;Zhang et al, 2016;Wang et al, 2020), emotion/memory [hippocampus (HIPP), amygdala (AMY)] (Zhang et al, 2019), self-referential processing [posterior cingulate cortex (PCC), precuneus] (Li et al, 2018;Liu et al, 2019), interoception (insula) (Wang et al, 2020) and inhibitory control [dorsolateral prefrontal cortex (DLPFC), anterior cingulate cortex (ACC)] Hu et al, 2020), which those changes tend to be levels of normal weight subjects; and highlight their critical role playing in the longterm weight loss post-surgery (Behary and Miras, 2015;Lin and Qu, 2020). Meanwhile, for clinical treatment of gastrointestinal disease, there are other surgical procedures (i.e., stomach removal surgery for treating gastric cancer) which are similar to LSG by removing partial of the stomach (Kim et al, 2017;Omori et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Overeating in obesity have been strongly attributed to the imbalance between the reward and inhibitory control circuits which is a consequence of conditioned learning and the resetting of reward thresholds following the longterm consumption of large quantities of high-calorie foods (Volkow et al, 2011). Previous studies related to LSG showed changes in functions (i.e., activity) and structures (i.e., volume) in those above regions were associated with the weight-loss and the reduction in food craving after surgery (Faulconbridge et al, 2016;Wang et al, 2020). Recovery of brain abnormalities following surgery can be also recognized as the result of the conditioned learning of the restrictive feeding and the resetting of satiety induced reward (Duan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%